Trade marketing: possíveis conflitos no relacionamento com a força de vendas - Diniz, Geraldo Pereira (2009)
Nowadays’ competitive environment, concentration of retailers is a reality, the industry attempted to adjust its structure to meet the demands of the trade/customer. The study seeks to understand the determinants that drive the industry to develop new links with their customers in this new scenario. There are conflicts between the actors involved in the process, marked, notably, interests are not always similar.